Effectiveness of a home-based exercise program among patients with lower limb spasticity post-stroke: A randomized controlled trial - Shaomin Chen; Chang Lv; Jiaozhen Wu; Chengwei Zhou; Xiaolong Shui; Yi Wang (Elsevier, 2021)
Purpose: To evaluate the effectiveness of advanced practice nurse-guided home-based rehabilitation exercise program (HREPro) among patients with lower limb spasticity post-stroke. Methods: This randomized controlled study recruited 121 patients with lower limb spasticity post-stroke. Intervention (n = 59) and control (n = 62) groups underwent 12-month HREPro and conventional rehabilitation, respectively, after discharge. The Fugl-Meyer assessment of spasticity measurement, modified Ashworth scale of motor function, 10-Meter Walk Test of walking ability, and Barthel index of activities of daily living (ADL) were evaluated at 0, 3, 6, and 12 months after discharge. Results: Significant differences were found in spasticity degree, motor function, walking ability, and ADL at 6 and 12 months after discharge between the control and intervention groups. Lower limb spasticity and ADL in the intervention group were significantly improved. Conclusion: HREPro is effective for rehabilitation of patients with lower limb spasticity post-stroke and has favorable home application.